Some Properties of Intuitionistic Fuzzy Ideals of Γ-Rings: N. Palaniappan, P.S. Veerappan, M. Ramachandran - Team, Support (Thai Journal of Mathematics, 2011)
In this paper, using the notion of intuitionistic fuzzy ideals of Γ-rings, we study the properties of normal intuitionistic fuzzy ideals, completely normal intuitionistic fuzzy ideals and maximal intuitionistic fuzzy ideals of Γ-rings.